Haemostatic defect in non-immune patients with falciparum malaria: no evidence of diffuse intravascular coagulation. - Vreeken, J (1978)
Nine non-immune patients with imported falciparum malaria were examined for signs of diffuse intravascular coagulation (DIC). Although all had thrombocytopenia initially and some later had a decline in plasma fibrinogen concentrations, DIC was never detected, even in severely affected patients with coma and kidney damage. None of the patients were given heparin and all recovered without residual symptoms. Heparin administration should probably be considered only when clear-cut DIC, which possibly never occurs in falciparum malaria, has been demonstrated.